Faktor yang mempengaruhi deteksi kecurangan dalam persepsi auditor eksternal dan auditor internal - Lukman, Hendro; Harun, Viviani (Jurnal Akuntansi, 2018)
The purpose of this study was to determine the effect of pressure, opportunity and razionalitation (The fraud triangel) to detect fraud on the perception of the external auditor and the internal auditor. This research carried out many acts of fraud in companies in Indonesia although the company has been audited by an independent and the internal auditor function within the company. This study uses primary data by distributing questionnaires to staff public accounting firms and internal auditors in the company. The processing of data using SPSS. The results of this study indicate that pressure, opportunity and razionalization have positiveÃ‚Â  impact on the detection of fraud on the perception of the external auditor and the internal auditor. Therefore, it is suggested for the company to create good governance to minimixe the fraud, and for auditors have to well understanding business and procedure of company